PROBLEMATIKA ARAH KIBLAT DAN APLIKASI PERHITUNGANNYA - Muhammad Rasywan Syarif (State Institute of Islamic Studies (IAIN) Palu, 2012)
Abstract: This paper discusses the direction of qiblah to Mecca. This direction is determined from any point or place on the earth's surface through the calculation and measurement procedures. Therefore, it is basically a kind of measurement to determine a direction to which Ka’bah can be seen from any point or place on the earth’s surface. Along with advances in technology, at this time qiblah’s direction can be determined more accurately than in the period of the Prophet or in the early days when Islam arrived to Indonesia. Therefore, the accuracy of determining the qiblah’s direction is adjusted according to the ability and advance of technology in their days. The determination of position, direction and distance from one point to another can be carried out using mathematic method and assisted with visualization software in order that deviation in qiblah’s direction can be observed either in mosques or other buildings.Kata kunci: Masjid, Ka’bah, Arah kiblat